A randomized noninferiority crossover trial of corrected count increments and bleeding in thrombocytopenic hematology patients receiving 2‐ to 5‐ versus 6‐ or 7‐day–stored platelets. Issue 8 (27th February 2015) - MacLennan, Sheila; Harding, Kay; Llewelyn, Charlotte; Choo, Louise; Bakrania, Lekha; Massey, Edwin; Stanworth, Simon; Pendry, Kate; Williamson, Lorna M.
<x xml:space="preserve">Abstract</x> BACKGROUND Bacterial screening offers the possibility of extending platelet (PLT) storage to Day 7. We conducted a noninferiority, crossover trial comparing PLTs stored for 6 or 7 days versus 2 to 5 days. STUDY DESIGN AND METHODS Stable hematology patients were allocated to receive blocks of 2‐ to 5‐ and 6‐ or 7‐day PLTs in random order. The primary outcome was the proportion of successful transfusions during the first block, defined as a corrected count increment (CCI) of more than 4.5 at 8 to 24 hours posttransfusion. RESULTS Of 122 patients with an evaluable first block, 87 (71%) and 84 (69%) had successful transfusions after 2‐ to 5‐ and 6‐ or 7‐day PLTs of mean (SD) ages of 3.8 (1.0) and 6.4 (0.5) days, respectively. Six‐ or 7‐day PLTs were declared noninferior to 2‐ to 5‐day PLTs since the upper confidence interval (CI) limit was less than the predefined noninferiority margin of 10% (95% CI, −14.0% to 9.1%; p = 0.766). Logistic regression analysis gave an adjusted odds ratio of 0.86 (95% CI, 0.47‐1.58; p = 0.625). Mean (SD) 8‐ to 24‐hour CCIs were 9.4 (7.9) and 7.7 (7.1) after transfusion with 2‐ to 5‐ or 6‐ or 7‐day PLTs (95% CI, −3.31 to 0.03; p = 0.054). The proportions of days with bleeding scores of WHO Grade 2 or higher were 13% (38/297 days) and 11% (32/296 days; 95% CI, −3.2 to 7.2; p = 0.454). Median interval to next PLT transfusion (2 days) was unaffected (95% CI, −10.5 to 5.4; p = 0.531). CONCLUSION In hematology patients, there was no evidence that 6‐ or 7‐day PLTs were inferior to 2‐ to 5‐day PLTs, as measured by proportion of patients with successful transfusions, bleeding events, or interval to next transfusion.